The good and bad effects of statins on insulin sensitivity and secretion. (November 2014) - Muscogiuri, Giovanna; Sarno, Gerardo; Gastaldelli, Amalia; Savastano, Silvia; Ascione, Antonio; Colao, Annamaria; Orio, Francesco
Abstract Aims: Statins are the main lipid-lowering treatment in both primary and secondary prevention populations. Whether statins deteriorates glycemic control, predisposing to the onset of diabetes mellitus has been a matter of recent concern. Statins may accelerate progression to diabetes via molecular mechanisms that impact insulin sensitivity and secretion. In this review, we debate the relative effect of statins in driving insulin resistance and the impairment of insulin secretion. Methods: Narrative overview of the literature synthesizing the findings of literature was retrieved from searches of computerized databases, hand searches, and authoritative texts employing the key words "Statins", "Randomized Clinical Trial", "Insulin sensitivity", "Insulin resistance", "Insulin Secretion", "Diabetes Mellitus" alone and/or in combination. Results: The weight of clinical evidence suggests a worsening effect of statins on insulin resistance and secretion, anyway basic science studies did not find a clear molecular explanation, providing conflicting evidence regarding both the beneficial and the adverse effects of statin therapy on insulin sensitivity. Conclusions: Although most of the clinical studies suggest a worsening of insulin resistance and secretion, the cardiovascular benefits of statin therapy outweigh the risk of developing insulin resistance, thus the data suggest the need to treat dyslipidemia and to make patients aware of the possible risk of developing type 2 diabetes or, if they already are diabetic, of worsening their metabolic control.